2015
DOI: 10.1073/pnas.1500639112
|View full text |Cite
|
Sign up to set email alerts
|

Splicing inhibition of U2AF 65 leads to alternative exon skipping

Abstract: U2 snRNP auxiliary factor 65 kDa (U2AF 65 ) is a general splicing factor that contacts polypyrimidine (Py) tract and promotes prespliceosome assembly. In this report, we show that U2AF 65 stimulates alternative exon skipping in spinal muscular atrophy (SMA)-related survival motor neuron (SMN) pre-mRNA. A stronger 5′ splice-site mutation of alternative exon abolishes the stimulatory effects of U2AF 65 . U2AF 65 overexpression promotes its own binding only on the weaker, not the stronger, Py tract. We further d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 54 publications
4
54
0
Order By: Relevance
“…20 Similarly, studies utilizing human cell lines show that knockdown of U2AF2 shifts the splicing toward introns harboring strong polypyrimidine tracts, 21 and that U2AF2 dependency can be eliminated by replacement of a stronger 5ss. 22 In addition, in fission yeast S. pombe, a large number of introns remain efficiently spliced upon the inactivation of U2AF, 59 the U2AF2 homolog. In this case stronger 5ss and A/U-rich sequence in the 5 0 intronic region are associated with U2AF 59 -insensitive introns.…”
Section: Introductionmentioning
confidence: 99%
“…20 Similarly, studies utilizing human cell lines show that knockdown of U2AF2 shifts the splicing toward introns harboring strong polypyrimidine tracts, 21 and that U2AF2 dependency can be eliminated by replacement of a stronger 5ss. 22 In addition, in fission yeast S. pombe, a large number of introns remain efficiently spliced upon the inactivation of U2AF, 59 the U2AF2 homolog. In this case stronger 5ss and A/U-rich sequence in the 5 0 intronic region are associated with U2AF 59 -insensitive introns.…”
Section: Introductionmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/199927 doi: bioRxiv preprint first posted online Oct. 8, 2017; is usually a rarer event in higher eukaryotes that contain longer introns 32 . We chose two longer intronic backbones (~300-600 bp) shown previously to not suffer from such intronic retention ( C. griseus DHFR and human SMN1 intron backbones), and found that the longer intron lengths improved both expression and assay reproducibility 33,34 . Exon inclusion metrics obtained from both of these intron contexts were highly reproducible between biological replicates (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…In this study, we investigated the regulatory role of U2AF65 in milk synthesis and growth of bovine mammary epithelial cells (BMECs). 7 The U2AF homology motif kinase 1 (UHMK1), a serine/threonine protein kinase, regulates the cell cycle via a tumour suppressor cyclin-dependent kinase inhibitor. Treatment with amino acids (Met and Leu) and hormones (prolactin and β-estradiol) upregulated the expression of U2AF65 in these cells.…”
mentioning
confidence: 99%